Mujeres fatales y desviados: nuevos deseos al asalto en el desfiladero de la literatura modernista - Bruce Marticorena, Enrique (2017)
This essay shed light over the connection between the literary style from the works of two "modernistas" authors: Julián del Casal and Delmira Agustini, and the cultural contexts and sexual mores at the end of the 19th century. The social dynamics of the ever expansive night life, the lurid and ubiquitous tabloids of the time and the growing interests towards deviant sexual behaviors and women's perspective in books, everything will align with certain guideline of the late Romanticism and Symbolism to shape new voices and expressions of desire. The Modernistas' retraction from sentimentalism and their maudit pose suit the remodeling of the sexual; the rarified object from the symbolist axiom dictates an evermore rarified new object: the one of the male body and its locus in the nascent representation of women's and deviants' libidos.